KARAKTERISASI EDIBLE FILM BERBASIS KITOSAN DARI LIMBAH KULIT UDANG DAN PATI SINGKONG SEBAGAI KEMASAN AKTIF ANTIMIKROBA - Khoerunnisa, Tiara Kurnia; Verdini, Liana; Soeherman, Giffary Primafisi; Hasibuan, Betti; Mahesya, Siti Roma (Jurnal Teknologi Pangan, 2025)
Packaging based on biodegradable materials is being widely used to overcome environmental problems. One way to overcome ecological problems is to make active edible films based on chitosan. This study examines the antimicrobial properties of chitosan by testing its antimicrobial activity.  This study aims to determine the potential of chitosan contained in shrimp shell waste as an edible antimicrobial film.  This study used the diffusion well method for chitosan and the diffusion disc for edible film.  The addition of chitosan to the edible film formula is 1:3, 1:1, and 3:1, the ratio between chitosan and cassava peel starch.  The results showed that the best characteristics were chitosan treatment: 3:1 starch and 45% glycerol addition (KP31C), with the best elongation at break value (3.541244%), best thickness (0.235 mm), and second largest tensile strength (1.026057 MPa) after Chitosan and Starch treatment 3:1 and 30% glycerol addition (KP31A